Case Report: Delayed Guillain-Barré syndrome following trauma: A case series and manage considerations - Zhang, Yiliu; Huang, Chuxin; Lu, Wei; Hu, Qing (Frontiers in Surgery, 2022)
Aim: To analyze clinical associations between Guillain-Barré syndrome (GBS) and trauma. Material and Methods: We retrospectively reviewed the data of eight patients with post-traumatic GBS between July 2011 and December 2018 at the Second Xiangya Hospital, China, and analyzed the triggers, clinical manifestation, examination results, treatment, prognosis, and potential mechanism related to post-traumatic GBS. Results: The included patients had GBS preceded by no risk factors other than trauma. Their age ranged from 15 to 60 years (the median age was 52 years), and six patients were males. The potential traumatic triggers included spinal surgery (n = 2), high-intensity exercise (n = 2), traumatic brain injury (n = 1), excessive fatigue (n = 1), ischemic stroke (n = 1), and cardiopulmonary resuscitation (n = 1). The major manifestation was symmetrical limb weakness and/or numbness in all patients. The diagnosis of GBS was based on the results of electromyography, albumino-cytological dissociation, or antiganglioside antibody in cerebrospinal fluid, and other diseases were excluded. Immunotherapy improved symptoms, except in one patient who died. Conclusions: Trauma is a probable risk factor for GBS that is very easily overlooked, thereby leading to misdiagnosis in clinical practice. We emphasize a new concept of post-traumatic GBS to promote doctors’ awareness when they meet people with weakness and sensory deficits after trauma, which benefit early diagnosis, timely treatment, and reduced mortality rate of GBS.